PENDIDIKAN PUASA DAN KESEHATAN MENTAL DALAM PERSPEKTIF PSIKOLOGI ISLAM - Miskahuddin Miskahuddin (Yayasan An-Nur Meunara Baro, 2025)
Ramadhan fasting is a spiritual practice with theological, psychological, and social dimensions. From an Islamic psychological perspective, fasting is understood as a process of spiritual education (tarbiyah nafs) aimed at fostering piety and mental balance. This article aims to comprehensively analyze the relationship between fasting education and mental health, based on Islamic psychological literature and contemporary empirical research. The method used is a literature review of international scientific journals and Islamic psychological studies. The analysis shows that Ramadhan fasting contributes to improved psychological well-being, emotional regulation, resilience, self-control, meaning in life, and social cohesion. Fasting also serves as a promotive-preventive intervention in spirituality-based mental health. By integrating classical Islamic concepts with modern scientific findings, fasting education can serve as a model